A pragmatic analysis of ostensible lies in high-context cultures - Saleem Abdelhady; Marwa Alkinj (Cogent Arts & Humanities, 2023)
This research investigates the pragmatic functions of ostensible lies in high-context cultures, with a specific focus on the Jordanian culture. Utilizing the Joint Action theory framework proposed by Clark (1996), the study aims to shed light on this communicative act. The data is collected through direct observation and recalls, and a qualitative analysis of 30 examples is conducted. The study reveals that ostensible lies in the Jordanian culture serve eight distinct off-record functions: implying information, expressing refusal, conveying rejection, extending apologies, expressing annoyance, engaging in bragging behavior, and adhering to regulations. These findings not only support the previously identified features of ostensible lies by Isaacs and Clark (1990) but also demonstrate potential overlap with the functions outlined in Walton’s (1998) study. However, the study adds an essential nuance by highlighting that in high-context cultures, ostensible lies can manifest even in situations where power dynamics are unequal, which challenges Walton’s argument. The significance of this study lies in its contribution to the understanding of lying behaviors within high-context cultures, particularly in the Jordanian context. By exploring the pragmatic functions of ostensible lies, the research enriches the existing literature on cross-cultural communication. It sheds light on the complexity and subtleties of communication practices in such cultural contexts. The findings have implications for intercultural communication, as they provide valuable insights for individuals and organizations seeking to navigate communication dynamics in high-context cultures, fostering more effective and culturally sensitive interactions.